Investigating the effect of dehydromiltirone on septic AKI using a network pharmacology method, molecular docking, and experimental validation - Chen, Sijia; Wang, Yanzhe; Liu, Yuyuan; Bai, Linnan; Li, Fengqin; Wu, Yue; Xie, Xinmiao; Zhang, Nan; Zeng, Chuchu; Zhang, Ling; Wang, Xiaoxia (Frontiers in Pharmacology, 2023)
Acute kidney injury (AKI) is a severe and frequent complication of sepsis in the intensive care unit, with inflammation and rapid decline of renal function as the main pathological features. Systemic inflammation, microvascular dysfunction and tubule injury are considered to be the main causes of sepsis-induced AKI (SI-AKI). The high prevalence and death rate of SI-AKI has brought great challenges to clinical treatment worldwide. But in addition to hemodialysis, there is a lack of effective drugs to improve renal tissue damage and alleviate the decline of kidney function. We conducted a network pharmacological analysis of a traditional Chinese medicine Salvia miltiorrhiza (SM), which is widely used in treatment of kidney disease. Then combined with molecular docking and molecular dynamics simulation to screen for the active monomer Dehydromiltirone (DHT) with therapeutic effects on SI-AKI and to investigate its potential mechanism of action through experimental validation. The components and targets of SM were obtained by searching the database, and 32 overlapped genes were screened by intersection analysis with AKI targets. The data of GO and KEGG showed that the functions of common gene were closely related to oxidative stress, mitochondrial function and apoptosis. Molecular docking results combined with molecular dynamics simulations provide evidence for the binding model between DHT and Cyclooxygenase-2 (COX2), both of which are mainly driven by van der Waals interactions and hydrophobic effect. In vivo, we found that mice pretreated by intraperitoneal injection of DHT (20 mg·kg−1·d−1) for 3 days ameliorated CLP surgery-induced renal function loss, renal tissue damage, and inhibited inflammatory mediators IL-6, IL-1β, TNF-α, and MCP-1 production. In vitro, DHT pretreatment decreased LPS-induced the expression of COX2, inhibited cell death and oxidative stress, alleviated mitochondrial dysfunction and restrained apoptosis in HK-2 cells. Our research indicated that the renal preventive effect of DHT is related to maintaining mitochondrial dynamic balance, restoring mitochondrial oxidative phosphorylation and inhibiting cell apoptosis. Findings in this study provide a theoretical basis and a novel method for the clinical therapy of SI-AKI.